Should male doctors in Sri Lanka wear a necktie to be recognized and respected? - Prabath K Abeysundara; Nilanga Nishad; Karthiha Balendran; Manod Pabasara; Poornima K Bandara; Narmada M Perera; Heshani De Silva; Shamila De Silva; Maheswaran Umakanth; Prasantha Wijesinghe (Journal of Infection in Developing Countries)
Introduction: European cultural norms have influenced physicians’ attire in Sri Lanka. The necktie is one such item of clothing which is worn to be recognized and respected as professionals. This study was carried out to assess the perceptions of doctors and patients towards male doctors wearing neckties while providing patient care.